Evaluating Tourism Performance through Tourist Perceptions: A Case Study of Petengoran Mangrove Tourism in Lampung, Indonesia - Murniati, Ktut; Riantini, Maya; Windyata, Ayla Vilin (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
The existence of components that did not represent the concept of ecotourism and the decline in the number of visits was very significant. This research evaluated tourism performance based on tourists’ perspectives to determine the components that need improvement. The respondents in this study were 100 tourists, who were obtained by applying the Slovin formula. This study used primary data collected through research questionnaires distributed to respondents. The research instrument was tested to ensure its validity and reliability. The collected data were analyzed using the Customer Satisfaction Index (CSI), Gap Analysis, and Importance-Performance Analysis (IPA). Petengoran Mangrove Tourism does not match tourists’ expectations. The attributes that become the main priority because their performance is considered not to have met tourists’ expectations are the availability and diversity of tourist activities, accessibility conditions, implementation of educational activities, and several facilities that do not meet tourist satisfaction, even though these components are what tourists highly expected. Keywords: customer satisfaction index, mangrove tourism, Petengoran, tourism performance, tourist perception